IDENTIFICATION AND TREATMENT OF ERYTHEMA MULTIFORME INDUCED BY ALLOPURINOL - I Nyoman Gede Juwita Putra; Raziv Ganesha; I Gusti Ngurah Putra Dermawan (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Introduction: Allopurinol is a xanthine oxidase inhibitor and has become established as the drug of choice for preventing and treating chronic gout. Erythema multiforme (EM) is an immune-mediated reaction that involves the skin and sometimes the mucosa. Many cases of EM are caused by drugs, one of which is allopurinol. The purpose of the case study is to explain the identification of allopurinol as a predisposing factor for EM and how it is treated. Case. A 56-year-old woman came with complaints of scabs on her lips for 1 week ago, and had been treated with corticosteroid ointment for 3 days. Extraoral examination showed hemorrhagic crusts on the upper and lower lips with erosive surrounded by erythematous margins. On the extremity found a target lesion on the right hand. Based on the examination, the patient was diagnosed with Erythema Multiforme with a differential diagnosis of herpes labialis and herpes associated erythema multiforme. Case Management. The therapy in this case was giving antihistamines for 1 week, NaCl 0.9% compresses on the lips for 30 minutes 3 times a day, after 2 weeks of treatment added with the application of 1% hydrocortisone cream as an anti-inflammatory and petroleum jelly on the lips as a moisturizer. Conclusion. Identification of the etiology of this EM case was carried out through anamnesis and history of drugs consumed as well as administration of topical corticosteroids as anti-inflammatories and oral antihistamines to reduce allergic reactions.